Towards the Exploration and Evolution of Insulin-like Venoms in Actiniaria (Sea anemones) - Alonso Delgado; Kyle S. Sozanski; Marymegan Daly (Marine Drugs, 2024)
Recent studies have elucidated the diversity of genes encoding venom in Sea anemones. However, most of those genes are yet to be explored in an evolutionary context. Insulin is a common peptide across metazoans and has been coopted into a predatory venom in many venomous lineages. In this study, we focus on the diversity of insulin-derived venoms in Sea anemones and on elucidating their evolutionary history. We sourced data for 34 species of Sea anemones and found sequences belonging to two venom families which have Insulin PFAM annotations. Our findings show that both families have undergone duplication events. Members of each of the independently evolving clades have consistent predicted protein structures and distinct dN/dS values. Our work also shows that sequences allied with VP302 are part of a multidomain venom contig and have experienced a secondary gain into the venom system of cuticulate Sea anemones.